Absolute frequencies of water lines near 790 nm with 10−11 accuracy. (January 2018) - Chen, J.; Hua, T.-P.; Tao, L.-G.; Sun, Y.R.; Liu, A.-W.; Hu, S.-M.
Highlights: Several water lines near 790 nm, in the 013-000 band of H2 16 O are recorded with comb-locked cavity ring-down saturation spectroscopy. Line positions are determined with an uncertainty of 25 kHz (relatively 6.6 × 10 −11 ), over one order of magnitude more accurate in a previous study. Upper energies of these transitions are determined with an accuracy of 10 −6 cm −1, indicating that the IUPAC-reported energies are inaccurate within 0.001 cm −1 . Abstract: Water lines in the infrared are convenient frequency references. We present absolute positions of several H2 16 O ro-vibrational transitions around 790 nm using comb-locked cavity ring-down saturation spectroscopy. Lamb dips of 6 water lines with saturation power in the range of 70–130 kW/cm 2 were observed and the line positions were determined with an accuracy of 25 kHz, corresponding to a fractional uncertainty of 6.6 × 10 −11 . The present work demonstrates the capability to considerably improve the accuracy of the water line positions in the infrared. Graphical abstract: